(untitled) (PERcursos Linguísticos, 2019)
When a young black reader believes all literature characters are white and blue-eyed, we are faced with one of the manifestations of the hegemony of certain countries or languages, materialized in their literary productions. Taking Adichie’s (2009) “single story” ideology as a starting point, this article intends to highlight the role of literary translation as a social practice, which can play a crucial role in the current political economy of fight against this inequality, especially in its relations with minority cultures. In this sense, the concepts of domestication and foreignization in translation, proposed by Venuti (1995), as alternative to the translator’s invisibility issue, as well as to Anglo-American cultural hegemony come to meet the fear of a “cultural homogenization” (HALL, 1997) or a “single story” in books. Through the use of specific methods, translation stands as a form of resistance, advocating from a perspective of the ethics of difference, encouraging the flowering of stories yet little known.